//// For G(x) = -1/4x - 1////
G(-5) = -1/4(-5) - 1 = 0.25;
G(-2) = -1/4(-2) - 1 = -0.25;
G(-1) = -1/4(-1) - 1 = -0.75;
///////////////////////////////////
////For G(x) = (x-1)^2 - 3////
G(-1) = ((-1) -1)^2 - 3 = 1;
G(-2) = ((-2) - 1)^2 - 3 = 6;
G(-5) = ((-5) - 1)^2 - 3 = 33;
//////////////////////////////////////////
////For G(x) = 1/4x + 2////////
G(-5) = 1/4(-5) + 2 = 0.75;
G(-2) = 1/4(-2) + 2 = 1.5;
G(-1) = 1/4(-1) + 2 = 1.75;
Answer:
f(3) = 36
Step-by-step explanation:
ƒ(x) = 5x^2 − 9x + 18
Let x =3
ƒ(3) = 5(3)^2 − 9(3) + 18
= 5*9 -27 +18
= 45 -27+18
=36
Answer:
68.338
Step-by-step explanation:
to know how much is less than we have to substract
74.14-5.802=68.338